Spinopelvic sagittal balance: what does the radiologist need to know? - Savarese,Leonor Garbin (2020)
Sagittal balance describes the optimal alignment of the spine in the sagittal plane, resulting from the interaction between the spine and lower limbs, via the pelvis. Understanding sagittal balance has gained importance, especially in the last decade, because sagittal imbalance correlates directly with disability and pain. Diseases that alter that balance cause sagittal malalignment and may trigger compensatory mechanisms. Certain radiographic parameters have been shown to be clinically relevant and to correlate with clinical scores in the evaluation of spinopelvic alignment. This article aims to provide a comprehensive review of the literature on the spinopelvic parameters that are most relevant in clinical practice, as well as to describe compensatory mechanisms of the pelvis and lower limbs.